Collaborative learning to improve communication skills in information and communication technology subjects - Rizki Koirum Hasibuan; Detri Amelia Chandra; Sri Wahyudi; Agung Setiawan (Institute of Computer Science (IOCS), 2023)
The process of learning and teaching in vocational schools must be standardized to the needs. Learning models, methods and media must support mastery of communication skills (Communication Skill). The aim of this research is to find out how effective the use of E-learning and Collaborative Learning is to improve Communication Skill on information and communication technology. Linearity test concluded that there is a significant linear relationship between each independent variable (Use of E-front and Collaborative Learning) with Improved Communication Skill. The normality test to get the results of the research data is not normally distributed, so the data is included in non-parametric statistics and uses the Mann-Whitney U test to get results that between the research class and the control class there are differences in learning outcomes in information and communication technology.